PERANAN WAKAF PRODUKTIF TERHADAP KEBERLANGSUNGAN USAHA MIKRO KECIL MENENGAH (UMKM) DAN KESINAMBUNGAN BADAN WAKAF WALISONGO - Nursyifa Yolanda (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
Wakaf management of UMKM pondok pesantren Wali Songo agency is managed productively and orderly. This research is aimed at knowing: 1) the influence of productive wakaf toward UMKM, 2) the influence of productive wakaf toward Wali Songo wakaf agency. This research used qualitative descriptive method. The data collecting technique used were observation, interview, and documentation. The prime data were obtained from observation and interview with KUA Pontianak chief official, managers of Wali Songo wakaf agency and UMKM owner. Meanwhile, the minor data were gained from documents of productive wakaf. Based on the result of the research, it can be inferred that: 1) Productive wakaf influenced UMKM productivity. The influences can be seen from kinds of business owned by pondok pesantren Wali Songo. 2) Productive Wakaf has vital role in wakaf agency